2013
DOI: 10.3389/fimmu.2013.00480
|View full text |Cite
|
Sign up to set email alerts
|

l-Citrulline Protects from Kidney Damage in Type 1 Diabetic Mice

Abstract: Rationale: Diabetic nephropathy (DN) is a major cause of end-stage renal disease, associated with endothelial dysfunction. Chronic supplementation of l-arginine (l-arg), the substrate for endothelial nitric oxide synthase (eNOS), failed to improve vascular function. l-Citrulline (l-cit) supplementation not only increases l-arg synthesis, but also inhibits cytosolic arginase I, a competitor of eNOS for the use of l-arg, in the vasculature.Aims: To investigate whether l-cit treatment reduces DN in streptozotocin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 77 publications
(97 reference statements)
3
42
0
Order By: Relevance
“…Wu et al examined the effects of administering drinking water containing 63% watermelon pomace juice to zucker diabetic fatty (ZDF) rats for 4 weeks, and observed a significant increase in NO synthase and NOx (nitrite/nitrate) . Moreover, Romero et al reported significantly restored NO/ROS balance after treatment of human glomerular endothelial cells with 1 Mm L‐citrulline …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al examined the effects of administering drinking water containing 63% watermelon pomace juice to zucker diabetic fatty (ZDF) rats for 4 weeks, and observed a significant increase in NO synthase and NOx (nitrite/nitrate) . Moreover, Romero et al reported significantly restored NO/ROS balance after treatment of human glomerular endothelial cells with 1 Mm L‐citrulline …”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have examined the effects of citrulline and watermelon extract on NO synthesis, glycaemic status, lipid profile, oxidative stress and inflammation in diabetes; however, no systematic review has appraised the findings in this field thus far, to the best of our knowledge. The purpose of the present study was to summarize the available data and compare the results of recent studies on the metabolic effects of citrulline and watermelon extract in diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggest an important role of Arg-II in type 1 diabetic renal disease. However, another group demonstrates opposite effects, i.e., Arg-II deficiency accelerates some of the STZ-induced renal damages in mice (Romero et al, 2013). The discrepancy between the two studies is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether Arg-II is also involved in obesity-associated type 2 diabetic renal disease is not known. In contrast to these studies, a recent study suggests that lack of Arg-II even accelerates some of the diabetes-induced renal damages in type 1 diabetic mouse model (Romero et al, 2013). …”
Section: Introductionmentioning
confidence: 89%
“…With respect to diabetic nephropathy, two out or three rodent studies conclude that supplemental arginine or citrulline can impede onset of this disorder; in one of these studies, citrulline but not arginine was effective [193,194]. Several studies report that supplemental arginine aids wound healing in diabetic rats, likely reflecting a key role for eNOS in the wound healing process [195,196,197].…”
Section: Citrulline Can Counter the Adverse Impact Of Adma And Argmentioning
confidence: 99%